Regulation of Interleukin-6 Receptor Signaling by TNF Receptor-Associated Factor 2 and 5 During Differentiation of Inflammatory CD4+ T Cells - Nagashima, Hiroyuki; Ishii, Naoto; So, Takanori (Frontiers in Immunology, 2018)
There is growing evidence that tumor necrosis factor (TNF) receptor-associated factors (TRAFs) bind to unconventional membrane-bound receptors in many cell types and control their key signaling activity, in both positive and negative ways. TRAFs function in a variety of biological processes in health and disease, and dysregulation of TRAF expression or activity often leads to a patho-physiological outcome. We have identified a novel attribute of TRAF2 and TRAF5 in interleukin-6 (IL-6) receptor signaling in CD4+ T cells. TRAF2 and TRAF5 are highly expressed by naïve CD4+ T cells and constitutively bind to the signal-transducing receptor common chain gp130 via the C-terminal TRAF domain. The binding between TRAF and gp130 limits the early signaling activity of the IL-6 receptor complex by preventing proximal interaction of Janus kinases (JAKs) associated with gp130. In this reason, TRAF2 and TRAF5 in naïve CD4+ T cells negatively regulate IL-6-mediated activation of signal transducer and activator of transcription 3 (STAT3) that is required for the development of IL-17-secreting CD4+ TH17 cells. Indeed, Traf2-knockdown in differentiating Traf5-/- CD4+ T cells strongly promotes TH17 development. Traf5-/- donor CD4+ T cells exacerbate the development of neuroinflammation in experimental autoimmune encephalomyelitis (EAE) in wild-type recipient mice. In this review, we summarize the current understanding of the role for TRAF2 and TRAF5 in the regulation of IL-6-driven differentiation of pro-inflammatory CD4+ T cells, especially focusing on the molecular mechanism by which TRAF2 and TRAF5 inhibit the JAK-STAT pathway that is initiated in the IL-6 receptor signaling complex.